THE CONDUCTING TECHNIQUE - AN INSTRUMENT USED TO SOLVE THE ISSUE OF CONDUCTING CUTOFFS AND THE "UNA BATTUTA" TIME BEATING TECHNIQUE - GUŢANU STOIAN, Luminiţa (Studia Universitatis Babes-Bolyai Musica, 2017)
The present study tackles the issue of conducting cut-offs and comes with solutions for solving them. It comprises all types of cut-offs, with detailed explanations on how to execute them, through diagrams and practical exercises. The same pattern is applied when presenting the second subject – the “una battuta” time beating technique. This study is intended to act as a handbook to student conductors, in their attempt of getting acquainted with the basics of conducting.